Synthesis and evaluation of antitumor activity of some thiazolo[4,5-b]pyridines - Chaban, T.I.; Panchuk, R.R.; Klenina, O.V.; Skorokhyd, N.R.; Ogurtsov, V.V.; Chaban, I.G. (Вiopolymers and Cell, 2012)
Aim. To synthesize a series of novel 3H-thiazolo[4,5-b]pyridine-2-ones by structural modification of the core heterocycle in its N3- and N6-positions and to evaluate their anticancer activity in vitro on several tumor cell lines. Methods. Organic synthesis, 1 H-NMR spectroscopy, trypan blue cell viability assay. Results. A new convenient synthetic approach was developed and optimized conditions were studied for the reaction of preparation of 3Hthiazolo[4,5-b]pyridin-2-one derivatives. 5,7-Dimethyl-3H-thiazolo[4,5-b]pyridin-2-one and 6-phenylazo-5,7- dimethyl-3H-thiazolo[4,5-b]pyridin-2-one were obtained by [3 + 3]cyclocondensation of 4-iminothiazolidone2 with acetylacetone and -phenylazoacetylacetone in methanol medium in the presence of sodium methylate. They were used as starting compounds for further structural modification of the core thiazolo[4,5-b]pyridine heterocycle in its 3- and 6-positions. On the basis of in vitro cytotoxicity studies of synthesized compounds several structure-functional relationships underlying anticancer potential of 5,7-dimethyl-3H-thiazolo[4,5-b]pyridin2-one derivatives were identified. Conclusions. 3H-thiazolo[4,5-b]pyridin-2-one can be considered as a promising molecular scaffold for rational design of potential anticancer drug candidates. Introduction of phenylazo substitute at C6-position of 3H-thiazolo[4,5-b]pyridin-2-one proved to be the most efficient, as it led to 3-fold increase of its anticancer potential. Keywords: thiazolo[4,5-b]pyridines, [3+ 3]cyclocondensation, structural modification, antitumor activity